Unconscious motivation. Part I: Implicit attitudes toward L2 speakers - Al-Hoorie, Ali H. (Studies in Second Language Learning and Teaching, 2016)
This paper reports the first investigation in the second language acquisition field assessing learners’ implicit attitudes using the Implicit Association Test, a computerized reaction-time measure. Examination of the explicit and implicit attitudes of Arab learners of English (N = 365) showed that, particularly for males, implicit attitudes toward L2 speakers are associated with self-reported openness to the L2 group and with strength of correlations among attitudinal and motivational variables. Implicit attitudes also moderated important paths in the L2 Motivational Self System. The paper concludes that implicit attitudes seem to be a meaningful individual difference variable, adding a new dimension to our understanding of language motivation.